The Influence of Business Environment and Capabilities on Transient Competitive Advantage and Their implications for Business Performance of Micro, Small and Medium Enterprises in Indonesia - Hermina, Nurul; Mariana, Adjeng; Kaniawati, Keni (International Journal of Engineering and Technology, 2018)
Micro, small and medium enterprises (MSME â€“ Indonesian: UMKM â€“ Usaha Micro, Kecil dan Menengah) are the key to increase growth, create employment, act as the source of peopleâ€™s income, to fulfil the need of goods and services, to increase the added values which eventually influence the economic growth. This research is aimed to explain how business environment and capability influence the competitive advantage which plays an important role that determines the business performance of MSME. The total sample able to be collected with web-based design is 56 MSME/UMKM from all over Indonesia. The analysis technique used is structural equation modeling (SEM). The study proves that business environment does not significantly influence the business performance of MSME/UMKM. However, this variable contributes significant indirect influence with a greater level than its direct influence. The finding indicates that improvement in business environment will be able to boost the business performance if it is combined with the improvement in competitive advantage of the MSME/UMKM. Â Â Â